Estudo das propriedades de blendas de biopoliamidas PA610 e PA1010 e análise de miscibilidade - Polkowski, Rodrigo Denizarte de Oliveira (2019)
In the present work, blends with biobased polymers (biopolyamides) were produced in several concentrations, aiming to identify the existence of interaction between the constituent elements and the effect of this interaction in their thermal, mechanical and morphological properties. The blends of biopolyamides 610 and 1010 (PA610 and PA1010) were prepared by mechanical mixing in the molten state by extrusion process. The specimens for blend characterization were prepared by injection molding process and the test conditions (temperature, relative humidity, holding time, etc.) followed the procedures prescribed by ISO 291 (2008). The experimental results revealed that there was no loss or degradation of mechanical properties, presenting intermediate values to the pure polymers. Through the DMTA testing it was possible to identify a single glass transition temperature (Tg) for each formulation, suggesting miscibility in the amorphous phase of the PA610/PA1010 blends. In the DSC curves, the crystallization of both components was observed, however, it was not possible to visualize the presence of significant domains in the morphological analysis of the blends (SEM and POM), characterizing a homogeneous mixture with good dispersion of the components. By confirming the depression of the equilibrium melting temperatures and obtaining negative values for the interaction parameters (x12) of these materials, it was possible to evidence that blends of the biopolyamides 610 and 1010 are fully miscible in all compositions.